VO2Max Level of Convicted Students at Special Prisons for Child Development Institution (LPKA) Class II Bengkulu - Yahya Eko Nopiyanto; Diah Ayu Aguspa Dita; Dian Pujianto; Mas’ullah Andriyani; Fiona Sarah Musfita; Zahra Putri Amelia (UNIB Press, 2023)
The level of VO2 max has significance in relation to both physical activity and health. Nevertheless, it should be noted that there has been a lack of VO2Max tests conducted on convicted children at LPKA Class II Bengkulu. Therefore, this study aims to determine the VO2 max level among convicted children at LPKA Class II Bengkulu. This study used a quantitative descriptive approach to examine a sample of 91 children between the aged of 14 and 19 years. The VO2 max level test uses a multi-stage fitness test. The analysis of the research data involved the utilization of descriptive quantitative percentages, which were employed to compare the category tables. The study's findings indicated that a proportion of 1.1% exhibited VO2 max levels falling within the lower group, while a substantial majority of 98.90% showed VO2 max levels falling within the significantly lower category. Based on the study results, it was concluded that convicted children at LPKA Class II Bengkulu exhibited VO2Max levels that fell within the extremely bad range. Based on the findings of this study, LPKA supervisors should devise and execute a physical coaching regimen to enhance the VO2 max levels among convicted children.